Theory and application of special functions : proceedings of an advanced seminar sponsored by the Mathematics Research Center, the University of Wisconsin-Madison, March 31-April 2, 1975 - Askey, Richard (Publication ... of the Mathematics Research Center, the University of Wisconsin--Madison ;, 1975)
Theory and Application of Special Functions.